Subacute Combined Degeneration of Spinal Cord - The Only Manifestation in an Otherwise “Normal” Vitamin B12 Deficient Patient - Raval, MD, Dr Darshankumar Manubhai; Trivedi, Nritya Brijesh; Trivedi, Shraddha; Vaghasiya, Yash; Parida, Aditi (International Journal of Innovative Research in Medical Science, 2022)
Sub-acute combined degeneration (SACD) is a myelopathy associated with vitamin B12 deficiency. Vitamin B12 deficiency may be asymptomatic or present with neurological and/or hematological features - neurological features such as myelopathy, neuropathy, dementia/neuropsychiatric abnormalities and rarely optic atrophy commonly presenting at a later stage than hematological changes. We present a case of a 15-year-old female who presented with ataxia, paresthesia and learning disability but no clinical symptoms or hematological evidence suggesting vitamin B12 deficiency. Our case report highlights the importance of early diagnosis and prompt treatment of vitamin B12 deficiency in a patient having only SACD as the disease’s manifestation.